PENGARUH KOMPETENSI, MOTIVASI DAN REWARD TERHADAP KINERJA KARYAWAN DAN VARIABEL SEMANGAT KERJA SEBAGAI VARIABEL INTERVENING PADA PEGAWAI DINAS PANGAN KABUPATEN SUKOHARJO - Yohanes Candra Purnama; Priscilla Uning; Agus Triatmono; Sri Isfantin Puji Lestari (JURNAL WIRANOMIKA, 2024)
Abstract : The formulation of the problem in this research is whether there is an influence of Competency on Work Morale? , Is there an influence of Motivation on Employee Performance?, Is there an influence of Rewards on Employee Performance?, Is there an influence of Competency on Employee Performance and Work Morale as an intervening variable?, Is there an influence of Motivation on Employee Performance and Work Morale as an intervening variable?, Is there an influence of Motivation on Employee Performance and Work Morale as an intervening variable? Is there an influence of rewards on employee performance and work morale as an intervening variable for Sukoharjo Regency Food Service Employees? There is no influence of Competency on Work Morale. This is because the t-value is 0.153 with a significance level of 0.879. Because the significance level is 0.879 > 0.05. There is no influence of motivational spirit and has no effect on employee morale. The t-count value is 7.806 with a significance level of 0.000. Because the significance level is 7.806 < 0.05, the Reward variable influences the work morale of Sukoharjo Regency Food Service Employees. The t-value obtained was 2.695 with a significance level of 0.007. Because the significance level is 0.007 < 0.05, the Work Morale variable influences employee performance. The t-value obtained was 1.727 with a significance level of 0.085. Because the significance level is 0.085 > 0.05, the Motivation variable has no effect on the performance of Sukoharjo Regency Food Service Employees. The t-value obtained was 0.215 with a significance level of 0.830. Because the significance level is 0.830 > 0.05, the Reward variable has no effect on Employee Performance. The t-value obtained was 1.501 with a significance level of 0.134. Because the significance level is 0.134 > 0.05, the Reward variable has no effect on the performance of Sukoharjo Regency Food Service Employees. The value of the intervening variable, namely work enthusiasm, is 0.144 with a significance level of 0.885 > 0.05. This means that work enthusiasm does not directly affect the competency of the Sukoharjo Regency Food Service employees' performance. The value of the intervening variable, namely work enthusiasm, is 0.443 with a significance level of 0.658 > 0.05. This means that work enthusiasm does not indirectly influence motivation on the performance of Sukoharjo Regency Food Service employees. There is an influence of Rewards on employee performance and Work Morale as an intervening variable value, namely work morale of 2.656 with a significance level of 0.008 < 0.05. This means that work enthusiasm indirectly influences the competence of the performance of Sukoharjo Regency Food Service employees.Â Keywords: Competency, Motivation, Reward, Performance and Work MoraleÂ